Comb‐shaped guanidinium functionalized poly(ether sulfone)s for anion exchange membranes: Effects of the spacer types and lengths. Issue 8 (3rd February 2017) - Chen, Ying; Tao, Yanping; Wang, Jinlei; Yang, Shanzhong; Cheng, Sheng; Wei, Haibing; Ding, Yunsheng
ABSTRACT: A series of poly(ether sulfone)‐based anion exchange membranes (AEMs), tethering with guanidinium side chains with different spacers, were synthesized via azide‐alkyne cycloaddition, deprotection, and the subsequent ion exchange reactions. The designed polymer structures were verified by the 1 H NMR spectra. Because of the appropriate water uptake and formation of interconnected ionic clusters, the GPES‐3C with propyl spacer showed higher conductivity than the GPES‐1C and GPES‐9C, with methylene and nonyl spacers, respectively. Comparatively, the GPES‐EO AEM with two ethylene oxide (EO) spacers exhibited even higher conductivity, these can be interpreted by interconnectivity of ionic channels and hydrophilicity nature of the EO spacer. Additionally, although the GPES membranes displayed sufficient thermal stability, the chemical stability of as‐prepared materials needs to be much improved for fuel cell applications. Overall, these results demonstrated that the properties of "pendent‐type" AEM can be tuned facilely by the spacer types and lengths. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1313–1321 Abstract : A series of poly(ether sulfone)s tethering with guanidinium side chains are synthesized and characterized. The effects of length and hydrophilicity of flexible side chains on AEM properties, such as water uptake, conductivity, ionic phase separation, and thermal property, are investigated.